Analisis Percepatan Waktu Pada Proyek Showroom Nissan, Office Dan Workshop Di Kota Pekanbaru - Adelia, Tisya; Taufik, Hendra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
First and foremost thing in a planning process was completion time in a project management as a basis for the overall planning. Delays on the project completion resulted in an extension of construction time which may result expensive. Project management was very important during the project’s implementation to avoid problems that may lead to losses for both owner and contractor. Problem commonly happened in a project was cost budget and work time that usually exceed the plan. This research is aim to reduce delayed for around 84 days from the estimated time for Nissan’s Office and Workshop Project in Pekanbaru. Work acceleration could be conducted through 3 ways which was overtime addition, adding man power, and working shift system alternative. The only work analyzed was the structural work which experiencing critical path. As a result acceleration cost from overtime alternative was Rp 15.393.542,00. Overtime was taken for 4 hours a day. Adding man power was adjusted to the needs in the field, the result is Rp 25.500.000,00 and acceleration with system shift alternative is Rp 38.940.000,00. The most effective acceleration alternative with minimum cost is overtime addition.Keywords: Project acceleration, delayed, cost, duration, overtime.